Across and along-strike crustal structure variations of the western Afar margin and adjacent plateau: Insights from receiver functions analysis. (August 2022) - Ahmed, Abdulhakim; Doubre, Cecile; Leroy, Sylvie; Keir, Derek; Pagli, Carolina; Hammond, James O.S.; Ayele, Atalay; Be de Berc, Maxime; Grunberg, Marc; Vergne, Jerome; Pestourie, Romain; Mamo, Daniel; et al.
Abstract: We used teleseismic receiver function analysis to image the crustal structure beneath 24 broadband seismic stations densely deployed along two profiles traversing different structural units across the western Afar margin. Our high-resolution receiver function results image pronounced spatial variations in the crustal structure along the profiles and provide improved insights to understand how strain is partitioned in the crust during rifting. Beneath the western plateau next to northern Afar, the crust is likely felsic-to-intermediate in composition (average Vp/Vs 1.74), with a step like thinning of the crust from an average of 38 km beneath the western plateau to an average of 22 km beneath the marginal graben. Consistently thicker crust is observed beneath the southern profile (central Afar), showing four distinct regions of uniform crustal thickness: 1) an average crustal thickness of 42 km beneath the western plateau; 2) 34 km beneath the foothills area; 3) 28 km beneath the marginal graben and the wide extensional basin and 4) 21 km beneath the central rift axis. We use crustal thickness results to estimate a stretching factor β of 2.2 and 2.7 for central Afar and northern Afar respectively. Our estimated values are lower than β > 3.0 predicted from plate reconstructions, and we interpret that the variations are best explained by 2–5 km magmatic addition into the crust. The crustal composition beneath the southern profile is more complex with elevated Vp/Vs ratios ranging between 1.79 and 1.85 beneath the western plateau and marginal graben. This is consistent with a greater mafic component and best explained by crust altered by intrusions due to significant pre and syn-rift magmatic activity. Abnormally high Vp/Vs ratios of more than 1.90 are observed beneath the axial rift zone of central Afar, which most likely suggests the localization of partial melt within the crust. Highlights: Dominant tectonic deformation beneath northern Afar, and magma assisted rifting in central Afar. Our results show sharp Moho beneath the western plateau of northern and central Afar. Felsic and mafic crust beneath the western plateau at the latitude of northern and central Afar, respectively. Multi step crustal thinning from the plateau to the rift center associated with felsic to mafic crustal composition change toward the rift axis.